The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.32526/ennrj/20/202200119
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Derived from Sesbania sesban Plant as a Potential Low-Cost Adsorbent for Removal of Methylene Blue

Abstract: In this study, biochar made from the Sesbania sesban plant, under slow pyrolysis at 300°C was used to adsorb methylene blue (MB) in aqueous solution. The biochar properties were clarified by diverse analytical methods such as FTIR, SEM, and BET. The results indicated that the surface of biochar was relatively smooth, had porous texture, and stacked evenly. In addition, the biochar had a large specific surface area of 561.8 m2/g and the pHpzc value was 6.9. The effect of adsorbent dosage, initial pH, contact ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
3
0
2
Order By: Relevance
“…As the MB concentration increases, more MB molecules are available to interact with the biochar particles, leading to more MB molecules being adsorbed [25]. This trend is also consistent with previous studies on dye adsorption by biochar [16,[26][27]. Increasing the MB concentration generally increased the adsorption capacity but decreased the removal efficiency.…”
Section: 4) Mb Concentrationsupporting
confidence: 90%
See 2 more Smart Citations
“…As the MB concentration increases, more MB molecules are available to interact with the biochar particles, leading to more MB molecules being adsorbed [25]. This trend is also consistent with previous studies on dye adsorption by biochar [16,[26][27]. Increasing the MB concentration generally increased the adsorption capacity but decreased the removal efficiency.…”
Section: 4) Mb Concentrationsupporting
confidence: 90%
“…Previous studies have shown that as the amount of adsorbent increases, the adsorption capacity decreases while the MB removal efficiency increases [16,24]. In this study, a BM-WBCB dosage of 0.3 g was optimal for cost savings.…”
Section: 3) Dose Of Bm-wbcbmentioning
confidence: 81%
See 1 more Smart Citation
“…Durrani et al [107] performed isothermal tests using date palm-activated biochar for the adsorption of MB in water, whose values described the best result for Langmuir, where the maximum MB adsorption capacity was 666.00 mg g −1 . Similarly, the study by Trung Hiep et al [108] presented isotherm tests using biochar from the Sesbania sesban plant for the removal of MB in water. The results were best fitted to the Langmuir model, and its maximum adsorption capacity was 6.60 mg g −1 .…”
Section: Adsmentioning
confidence: 99%
“…Điều này chứng tỏ, tốc độ hấp phụ thuốc nhuộm MB có thể được kiểm soát phần lớn bởi một quá trình hấp phụ hóa học, kết hợp với với các đặc tính hóa học của than và MB. Kết quả này cũng tương đồng với kết quả của các công trình nghiên cứu sự hấp phụ MB lên các vật liệu khác nhau như than từ xương rồng -Opuntia ficus indica (Barka, 2013;Sakr et al, 2015), than từ cây điên điển (Hiep, 2022).…”
Section: Kết Quả Và Thảo Luận 31 Tính Chất Của Tsh đượC Sản Xuất Bằng...unclassified